Chaos-Complexity Theory and Education Policy: Lessons from Malawi's Community Day Secondary Schools - H.M. Kayuni (University of Sofia, 2010)
Since the democratic dispensation of 1994, the education sector seems to be in perpetual transition with numerous facets of policies being introduced against a background of alleged poor management, understaffing and a poorly paid cadre of teachers. The situation was at one time likened "to a patient on a resuscitation bed in a hospital". Despite this seemingly chaotic and complex scenario, the education system has managed to survive. Using the Malawi Community Day Secondary Schools (CDSS) policy, the paper intends to draw some insights from public policy's Chaos and Complexity theory to explain why the education sector still manages to survive and show resilience (on the "edge of chaos") despite the apparent overwhelming challenges.